GST in India : Performance of Companies After One - Year of Roll Out - Shukla, Shalini; Singh, Ram (Indian Journal of Finance, 2018)
There is mixed anticipation and different responses on GST from manufacturers, service providers, and different market intermediaries. There is lack of such studies, specifically in the context of India, that provide any empirical support on either positive or negative impact of GST. Thus, the present study sought to empirically analyze the performance of companies after one year of GST implementation. Probability sampling was used to get the relevant sample. A total of 192 BSE listed companies were taken for analysis. Financial parameters (total assets, profit, and market capitalization for FY2017 and FY 2018) and demographic variables (size and experience of companies) were used to analyze the impact of GST roll out. The results indicated that among all three financial parameters, only total assets were significantly different from the pre GST time (FY2017). Further analysis highlighted that age and size of the company also affected the equation and were found significant in influencing the performance of companies after GST implementation. Detailed analysis and results were subsequently discussed in this paper. The study brought forth new insights on effect of new indirect tax regime on financial performance of the companies in order to fill the research gap. The results of the study will be useful for policy makers, strategists, and managers to cope up with the challenges posed by GST.